Predicament of Landlessness: A Critical study of Women's Rights over Land in Assam. (March 2020) - Hazarika, Kanki; Sita, V.
Abstract: Land rights to women is one of the significant markers of a gender-just society. It is a basic human right that provides welfare, economic and social security, strong bargaining power and various other benefits. Ownership right over land is also critical to the citizens in terms of exercising and availing rights guaranteed by the state. Based on a narrative from the fieldwork done among the Bodos in Assam, this paper explores the significance of land rights in accessing various rights and welfare programmes and how women are affected in this regard due to lack of land rights. It discusses how a woman's lack of rights over land can lead to a status of homelessness and place her in a socially and economically precarious position. The landlessness or homelessness status restricts her from accessing various benefits provided by the state. In this context, the paper also looks into the social construction of gendered norms on land rights of the Bodo community. Construction of societal norms on individual's rights over landed property, inheritance are generally determined by kinship and affinal ideologies of a community. Such norms are often gendered that deny rights to women over this material resource. The most affected are the single, widow and separated women who have no support from the families. Communities having patriarchal ideologies consider women as passive, dependent and secondary subject and accordingly, gendered norms are constructed. Even the state apparatuses, which is often male-dominated, locate woman within the realm of the family and design policies for women as 'beneficiaries' and 'dependents.' The gendered norms on land rights of a community have a broader impact that goes beyond the community level and enmeshed with the affairs of the state.